An experimental examination of the effects of alcohol consumption and exposure to misleading postevent information on remembering a hypothetical rape scenario. Issue 3 (4th March 2019) - Flowe, Heather D.; Humphries, Joyce E.; Takarangi, Melanie K.; Zelek, Kasia; Karoğlu, Nilda; Gabbert, Fiona; Hope, Lorraine
Summary: We experimentally examined the effects of alcohol consumption and exposure to misleading postevent information on memory for a hypothetical interactive rape scenario. We used a 2 beverage (alcohol vs. tonic water) × 2 expectancy (told alcohol vs. told tonic) factorial design. Participants ( N = 80) were randomly assigned to conditions. They consumed alcohol (mean blood alcohol content = 0.06%) or tonic water before engaging in the scenario. Alcohol expectancy was controlled by telling participants they were consuming alcohol or tonic water alone, irrespective of the actual beverage they were consuming. Approximately a week later, participants were exposed to a misleading postevent narrative and then recalled the scenario and took a recognition test. Participants who were told that they had consumed alcohol rather than tonic reported fewer correct details, but they were no more likely to report incorrect or misleading information. The confidence–accuracy relationship for control and misled items was similar across groups, and there was some evidence that metacognitive discrimination was better for participants who were told that they had consumed alcohol compared with those told they had tonic water. Implications for interviewing rape victims are discussed.